Role of gut microbiota-derived signals in the regulation of gastrointestinal motility - Zheng, Zhipeng; Tang, Jingyi; Hu, Yingnan; Zhang, Wei (Frontiers in Medicine, 2022)
The gastrointestinal (GI) tract harbors trillions of commensal microbes, called the gut microbiota, which plays a significant role in the regulation of GI physiology, particularly GI motility. The GI tract expresses an array of receptors, such as toll-like receptors, G-protein coupled receptors, aryl hydrocarbon receptor, and ligand-gated ion channels, that sense different gut microbiota-derived bioactive substances. Specifically, microbial cell wall components and metabolites, including lipopeptides, peptidoglycan, lipopolysaccharides, bile acids, short-chain fatty acids, and tryptophan metabolites, mediate the effect of gut microbiota on GI motility through their close interactions with the enteroendocrine system, enteric nervous system, intestinal smooth muscle, and immune system. In turn, GI motility affects the colonization within the gut microbiota. However, the mechanisms by which gut microbiota interacts with GI motility remain to be elucidated. Deciphering the underlying mechanisms is greatly important for the prevention or treatment of GI dysmotility, which is a complication associated with many GI diseases, such as irritable bowel syndrome and constipation. In this perspective, we overview the current knowledge on the role of gut microbiota and its metabolites in the regulation of GI motility, highlighting the potential mechanisms, in an attempt to provide valuable clues for the development of gut microbiota-dependent therapy to improve GI motility.